Preparation method of carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material

By combining aramid nanofibers, biomass polyphenols and magnetic metal salts with polyvinyl alcohol, carbon/magnetic metal/aramid nanofiber composite aerogels, the problem of impedance mismatch of existing carbon-based absorbing materials is solved, excellent microwave absorption and mechanical properties are achieved, and a green and environmentally friendly preparation process is provided.

CN119410024BActive Publication Date: 2025-03-14SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510015893.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-14
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Existing carbon-based absorbing materials have poor impedance due to high conductivity and excessive dielectric constant, making it difficult to achieve excellent microwave absorption and mechanical properties.

Method used

By combining aramid nanofibers, biomass polyphenols and magnetic metal salts with polyvinyl alcohol, a carbon/magnetic metal/aramid nanofiber composite aerogel is formed, and the impedance matching is adjusted using hydrogen bonding and magnetic loss mechanisms to achieve strong absorption performance in broadband.

Benefits of technology

It realizes excellent microwave absorption performance and good mechanical properties of composite aerogels, can achieve wide-band strong absorption at a lower filling rate, and has a green and environmentally friendly preparation process with low equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410024B_ABST
    Figure CN119410024B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material, which belongs to the field of absorbing material preparation. The preparation method comprises the following steps: (1) respectively preparing a polyvinyl alcohol solution, an aramid nanofiber solution, a polyphenol solution and a magnetic metal salt solution. (2) sequentially adding the aramid nanofiber solution, the polyphenol solution and the magnetic metal salt solution to the polyvinyl alcohol solution, and stirring at room temperature to make the mixed solution uniformly dispersed. (3) pouring the uniformly dispersed solution into a mold, freezing and freeze-drying. (4) Finally, carbonizing the dried sample under an inert atmosphere to obtain a carbon / magnetic metal / aramid nanofiber composite aerogel. The present invention is simple to operate and environmentally friendly. The prepared carbon / magnetic metal / aramid nanofiber composite aerogel has excellent absorbing performance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of wave-absorbing materials, and in particular to a method for preparing a carbon / magnetic metal / aramid nanofiber composite aerogel wave-absorbing material. Background Art

[0002] The explosive growth of electronic communication technology has brought great convenience, but excessive electromagnetic waves (EMW) can also cause radiation pollution and equipment interference. Therefore, microwave absorbing materials (including ferrites, magnetic metal alloys, metal disulfides, conductive polymers, and carbon-based materials) that can convert electromagnetic waves into heat energy have been developed to solve these problems.

[0003] Among these absorbing materials, carbon-based materials have the advantages of strong microwave absorption ability (MA), low density and excellent environmental stability. However, pure carbon materials often have impedance mismatch problems due to their high conductivity and excessively high dielectric constant. At present, some research has been carried out to overcome this defect. For example, Yu et al. introduced FeNi alloy and TiN into a melamine-based carbon foam skeleton, and the minimum reflection loss (RL) of the resulting composite material at 1.3 mm was -24.83 dB (Advanced Electronic Materials, 2024, 2400265). In summary, constructing a porous structure and introducing multiple loss mechanisms are two ways to adjust impedance matching and improve the absorbing performance of carbon materials.

[0004] Recently, in addition to wave absorption performance, other requirements have been put forward when coating the surface of civilian electronic equipment and military stealth aircraft with wave absorption materials to reduce signal interference and radar detection. For example, excellent mechanical properties can prevent aircraft deformation in harsh environments. Wang et al. doped inorganic Fe7S8 into honeycomb porous carbon nanofibers (Fe7S8 / PCNF) and aramid nanofibers (ANF). The obtained Fe7S8 / PCNF@ANF nanofiber hybrid aerogel has a compressive stress retention rate of over 95% after 100 cycles at 40% strain, and the aerogel achieves an absorption of -37.0dB at 15.7GHz. (ACS Applied Nano Materials, 2024, 7, 4130-4142).

[0005] Although the above strategies have been improved, it is still a challenge to prepare high-performance absorbing materials by simple and environmentally friendly methods. Metal polyphenol framework (MPN) connects organic ligands with biomass polyphenols (tannic acid, gallic acid, etc.), which is similar to the metal organic framework structure and has the advantages of abundant sources, environmental friendliness and low price. The magnetic metal formed by pyrolysis / carbonization of the metal-polyphenol framework can be evenly distributed in the porous carbon network framework and used as a magnetic loss component to adjust the impedance matching of the porous carbon, thereby achieving broadband strong absorption performance. The present invention prepares carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material by enhancing the mechanical properties of polyvinyl alcohol-based aerogel with aramid nanofibers. This type of aerogel has not only excellent microwave absorption performance, but also good mechanical properties. In addition, polyvinyl alcohol and metal-polyphenol framework can form a three-dimensional porous structure after carbonization, and magnetic metal particles are attached to the porous carbon framework. The porous carbon framework and magnetic metal particles make the composite aerogel have excellent impedance matching and multiple loss mechanisms, greatly enhancing the microwave absorption capacity of the composite aerogel. The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material has a simple preparation process, is green and environmentally friendly, has low equipment requirements, and is highly controllable. It is a type of material with broad application prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material with excellent microwave absorption performance and good mechanical properties. The preparation process is simple and green, the raw materials are easily available, and the equipment requirements are low.

[0007] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing a carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material, comprising the following steps:

[0008] S1: preparing a polyvinyl alcohol solution with a concentration of 50-100 mg / mL, an aramid nanofiber solution with a concentration of 5-10 mg / mL, a polyphenol solution with a concentration of 5-20 mg / mL, and a magnetic metal salt solution with a concentration of 5-20 mg / mL respectively;

[0009] S2: adding the aramid nanofiber solution, the polyphenol solution and the magnetic metal salt solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to make the mixed solution evenly dispersed;

[0010] S3: pouring the uniformly dispersed polyvinyl alcohol / magnetic metal-polyphenol framework / aramid nanofiber solution into a mold and freezing it and freeze-drying it for 72 h;

[0011] S4: The dried sample is carbonized under an inert atmosphere to obtain a carbon / magnetic metal / aramid nanofiber composite aerogel;

[0012] Preferably, the polyphenol is one or a combination of tannic acid, gallic acid, and tannic acid, and the magnetic metal salt is a water-soluble salt, wherein the metal ion is Fe 3+ , Fe 2+ 、Co 2+ 、Ni 2+ One or a combination of the following, wherein the metal salt is one of sulfate, chloride and nitrate.

[0013] Preferably, the volume of the polyvinyl alcohol solution: the volume of the aramid nanofiber solution: the volume of the polyphenol solution: the volume of the metal salt solution = 4:2:1:1 to 8:6:1:1.

[0014] Preferably, the metal-polyphenol framework is Fe 3+ -Tannic acid, Fe 2+ -Tannic acid, Co 2+ - Tannic acid, Ni 2+ -Tannic acid, Fe 3+ -Hydroxyacetic acid, Fe 2+ -Hydroxycholic acid, Co 2+ -Hydroxyacetic acid, Ni 2+ -Hydroxyacetic acid, Fe 3+ -Gallic acid, Fe 2+ -Gallic acid, Co 2+ -Gallic acid, Ni 2+ - One or a combination of gallic acid.

[0015] Preferably, the inert atmosphere is nitrogen or argon, the heating rate is 5-10°C / min, the temperature range is 600-800°C, and the carbonization time is 2-4h.

[0016] Preferably, the magnetic metal is Fe, Co, Ni or a combination of several thereof.

[0017] The present invention has at least the following excellent effects:

[0018] (1) The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material provided by the present invention is made of polyvinyl alcohol, biomass polyphenols, soluble magnetic metal salts and aramid nanofibers as raw materials, and water as solvent. The mechanical properties of polyvinyl alcohol aerogel are enhanced by hydrogen bonding between the amide group (-NH-OH) of aramid nanofibers and the hydroxyl group (-OH) of polyvinyl alcohol. Biomass polyphenols react with magnetic metal salts to form a metal-polyphenol framework that can be connected to polyvinyl alcohol through hydrogen bonds. Finally, carbonization is performed to obtain a carbon / magnetic metal / aramid nanofiber composite aerogel. The polyphenols used are biomass raw materials, which are green and environmentally friendly and can be repeatedly operated, meeting the current requirements of green environmental protection.

[0019] (2) The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material provided by the present invention, wherein the carbonization of polyvinyl alcohol can promote the reduction of metal ions into magnetic metals to provide magnetic loss, and the heterogeneous interface formed by the magnetic metal and carbon is conducive to promoting interface polarization; on the other hand, the composite aerogel will form defects after carbonization, which will enhance the polarization and dipole polarization caused by the defects under the alternating magnetic field. The porous carbon network structure formed by the carbonization of polyvinyl alcohol gel can promote the migration and jumping of electrons to enhance the conduction loss. Finally, the impedance matching of the composite material is improved through the synergistic effect of each component, so that microwaves can enter the absorbing material as much as possible.

[0020] (3) The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material provided by the present invention has good mechanical properties (capable of bearing 800-2500 times its own weight) and excellent absorbing performance.

[0021] (4) The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material provided by the present invention can achieve broadband strong absorption (effective absorption bandwidth is between 3 and 6 GHz, and the minimum reflection loss is between -20 and -75 dB) at a relatively low filling rate (20 to 30 wt%).

[0022] (5) The carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material provided by the present invention can regulate the microstructure and absorbing performance of the carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material by adjusting the ratio of polyvinyl alcohol, biomass polyphenols, metal salts, aramid nanofibers, carbonization temperature, carbonization time and other conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the carbon / Co / aramid nanofiber composite material prepared in Example 1 of the present invention.

[0024] Figure 2 This is the X-ray diffraction pattern of the carbon / Co / aramid nanofiber composite material prepared in Example 1 of the present invention.

[0025] Figure 3 This is a reflection loss diagram of the carbon / Co / aramid nanofiber composite material prepared in Example 1 of the present invention.

[0026] Figure 4 This is a rendering showing that the carbon / Co / aramid nanofiber composite material prepared in Example 1 of the present invention can withstand 1219 times its own weight. DETAILED DESCRIPTION

[0027] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. After understanding the embodiments of the present invention, any person skilled in the art can make changes and modifications based on the techniques taught by the present invention without departing from the spirit and scope of the present invention.

[0028] Test Method

[0029] The microscopic morphology was observed using a SU-3500 scanning electron microscope; the physical phase of the carbon / magnetic metal / aramid nanofiber composite aerogel was analyzed using a Shimadzu XRD-6100 X-ray diffractometer; the electromagnetic parameters of the sample were tested using a N5230A vector network analyzer, and the test method was the coaxial method. The sample to be tested was evenly mixed with paraffin in a certain proportion and pressed into a ring with an inner diameter of 3mm, an outer diameter of 7mm, and a thickness of 2mm. The electromagnetic parameters were tested in the range of 2~18GHz, and were fitted and analyzed using Matlab.

[0030] Example 1: S1: Prepare 20 mL of a 50 mg / mL polyvinyl alcohol solution, 10 mL of a 7.5 mg / mL aramid nanofiber solution, 5 mL of a 10 mg / mL tannic acid solution, and 5 mL of a 10 mg / mL cobalt chloride hexahydrate solution;

[0031] S2: adding the aramid nanofiber solution, tannic acid solution and cobalt chloride hexahydrate solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to make the mixed solution evenly dispersed;

[0032] S3: Dispersed polyvinyl alcohol / Co 2+ - The tannic acid framework / aramid nanofiber solution was poured into a mold and frozen and freeze-dried for 72 h;

[0033] S4: carbonizing the dried sample at 800°C for 2 h in a nitrogen atmosphere at a heating rate of 5°C / min to obtain a carbon / Co / aramid nanofiber composite material;

[0034] Figure 1 This is a scanning electron microscope image of the carbon / Co / aramid nanofiber composite material prepared in Example 1. Figure 2 is the X-ray diffraction pattern of the carbon / Co / aramid nanofiber composite material prepared in Example 1, Figure 3 This is a reflection loss diagram of the carbon / Co / aramid nanofiber composite material prepared in Example 1 with 25 wt% added to paraffin wax. Figure 4 This is a rendering showing that the carbon / Co / aramid nanofiber composite material prepared in Example 1 can withstand 1219 times its own weight. Figure 1 It can be seen that the composite material exhibits a rich three-dimensional porous structure, and the Co metal particles are distributed in the porous network skeleton; Figure 2 It can be seen that the XRD diffraction peaks of carbon / Co / aramid nanofiber composite aerogel have obvious Co (PDF#15-0806) characteristic peaks, which are basically consistent with the standard card. The diffraction peak at 25.2° corresponds to the carbon peak. Figure 3 It can be seen that the carbon / Co / aramid nanofiber composite aerogel exhibits excellent wave absorbing performance. The addition amount of the composite aerogel in paraffin is 25wt%, the minimum reflection loss is -65.2dB when the matching thickness is 2.48mm, and the effective absorption bandwidth is 4.48GHz when the matching thickness is 1.52mm. Figure 4 It shows that the carbon / Co / aramid nanofiber composite aerogel can withstand 1219 times its own weight and exhibits good mechanical properties.

[0035] Example 2: S1: Prepare 20 mL of a 50 mg / mL polyvinyl alcohol solution, 15 mL of a 10 mg / mL aramid nanofiber solution, 2.5 mL of a 7.5 mg / mL gallic acid solution, and 2.5 mL of a 7.5 mg / mL ferrous sulfate heptahydrate solution;

[0036] S2: adding the aramid nanofiber solution, gallic acid solution and ferrous sulfate heptahydrate solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to make the mixed solution evenly dispersed;

[0037] S3: Dispersed polyvinyl alcohol / Fe 2+ - The gallic acid framework / aramid nanofiber solution was poured into a mold and frozen and freeze-dried for 72 h;

[0038] S4: carbonizing the dried sample at 800°C for 2 h in an argon atmosphere at a heating rate of 10°C / min to obtain a carbon / Fe / aramid nanofiber composite material;

[0039] The carbon / Fe / aramid nanofiber composite material has a filling rate of 25wt% in paraffin and a matching thickness of 3mm. The minimum reflection loss is -38dB, the effective absorption bandwidth is 3.2GHz, and it can withstand 2100 times its own weight.

[0040] Example 3: S1: Prepare 20 mL of a 50 mg / mL polyvinyl alcohol solution, 10 mL of a 5 mg / mL aramid nanofiber solution, 2.5 mL of a 7.5 mg / mL scopolamine solution, and 2.5 mL of a 7.5 mg / mL nickel nitrate hexahydrate solution;

[0041] S2: adding the aramid nanofiber solution, the rubeic acid solution and the nickel nitrate hexahydrate solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to make the mixed solution evenly dispersed;

[0042] S3: Dispersed polyvinyl alcohol / Ni 2+ - The arachidonic acid framework / aramid nanofiber solution was poured into a mold and frozen and freeze-dried for 72 hours;

[0043] S4: carbonizing the dried sample at 600°C for 4 h in a nitrogen atmosphere at a heating rate of 5°C / min to obtain a carbon / Ni / aramid nanofiber composite material;

[0044] The carbon / Ni / aramid nanofiber composite material has a filling rate of 30wt% in paraffin and a matching thickness of 4mm. It has a minimum reflection loss of -25dB and an effective absorption bandwidth of 3.5GHz, and can withstand 2500 times its own weight.

[0045] Example 4: S1: Prepare 20 mL of a 60 mg / mL polyvinyl alcohol solution, 10 mL of a 10 mg / mL aramid nanofiber solution, 2.5 mL of a 5 mg / mL tannic acid solution, 2.5 mL of a 5 mg / mL scopolamine solution, and 5 mL of a 5 mg / mL ferric chloride hexahydrate solution;

[0046] S2: adding the aramid nanofiber solution, the mixed solution of tannic acid and linalool and the ferric chloride hexahydrate solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 hour to disperse the flocculent complex;

[0047] S3: Dispersed polyvinyl alcohol / Fe 3+ -Tannic acid framework / Fe 3+ - The arachidonic acid framework / aramid nanofiber solution was poured into a mold for directional freezing and freeze-dried for 72 hours;

[0048] S4: carbonizing the dried sample at 800°C for 3 h in a nitrogen atmosphere at a heating rate of 10°C / min to obtain a carbon / Fe / aramid nanofiber composite material;

[0049] The carbon / Fe / aramid nanofiber composite material has a filling rate of 25wt% in paraffin and a matching thickness of 2mm. The minimum reflection loss is -43dB, the effective absorption bandwidth is 4.2GHz, and it can withstand 800 times its own weight.

[0050] Example 5: S1: Prepare 20 mL of a 50 mg / mL polyvinyl alcohol solution, 10 mL of a 7.5 mg / mL aramid nanofiber solution, 5 mL of a 10 mg / mL tannic acid solution, 2.5 mL of a 10 mg / mL nickel chloride hexahydrate solution, and 2.5 mL of a 10 mg / mL cobalt chloride hexahydrate solution;

[0051] S2: adding the aramid nanofiber solution, tannic acid solution, nickel chloride hexahydrate and cobalt chloride hexahydrate solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to disperse the flocculent complex;

[0052] S3: Dispersed polyvinyl alcohol / Ni 2+ - Tannic acid frame / Co 2+ - The tannic acid framework / aramid nanofiber solution was poured into a mold and frozen and freeze-dried for 72 h;

[0053] S4: carbonizing the dried sample at 700°C for 4 h in a nitrogen atmosphere at a heating rate of 5°C / min to obtain a carbon / CoNi / aramid nanofiber composite material;

[0054] The carbon / CoNi / aramid nanofiber composite material has a filling rate of 25wt% in paraffin and a matching thickness of 2mm. The minimum reflection loss is -51dB, the effective absorption bandwidth is 4.3GHz, and it can withstand 1500 times its own weight.

Claims

1. A method for preparing a carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material, Its characteristics include the following steps: S1: prepare a polyvinyl alcohol solution with a concentration of 50-100 mg / mL, an aramid nanofiber solution with a concentration of 5-10 mg / mL, a polyphenol solution with a concentration of 5-20 mg / mL, and a magnetic metal salt solution with a concentration of 5-20 mg / mL, respectively, wherein the volume of the polyvinyl alcohol solution: the volume of the aramid nanofiber solution: the volume of the polyphenol solution: the volume of the magnetic metal salt solution = 4:2:1:1 to 8:6:1:1; S2: adding the aramid nanofiber solution, the polyphenol solution and the magnetic metal salt solution to the polyvinyl alcohol solution in sequence, and stirring at room temperature for 1 h to make the mixed solution evenly dispersed; S3: pouring the uniformly dispersed polyvinyl alcohol / magnetic metal-polyphenol framework / aramid nanofiber solution into a mold and freezing it and freeze-drying it for 72 h; S4: The dried sample is carbonized under an inert atmosphere to obtain a carbon / magnetic metal / aramid nanofiber composite aerogel; The density of the carbon / magnetic metal / aramid nanofiber composite aerogel is between 1 and 1.5 g / cm 3 When used as an absorbing material, the minimum reflection loss is between -30 and -75dB, the effective absorbing bandwidth is between 3 and 6GHz, and the mechanical properties can withstand 800-2500 times its own weight.

2. The method for preparing the carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material according to claim 1, characterized in that: The polyphenol is one or a combination of tannic acid, gallic acid, and tannic acid, and the magnetic metal salt is a water-soluble salt, wherein the magnetic metal ion is Fe 3+ , Fe 2+ 、Co 2+ 、Ni 2+ The magnetic metal salt is one of the sulfates, chlorides and nitrates of the above-mentioned metal ions.

3. The method for preparing the carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material according to claim 1, characterized in that: The magnetic metal-polyphenol framework is Fe 3+ -Tannic acid, Fe 2+ -Tannic acid, Co 2+ - Tannic acid, Ni 2+ -Tannic acid, Fe 3+ -Hydroxyacetic acid, Fe 2+ -Hydroxycholic acid, Co 2+ -Hydroxyacetic acid, Ni 2+ -Hydroxyacetic acid, Fe 3+ -Gallic acid, Fe 2+ -Gallic acid, Co 2+ -Gallic acid, Ni 2+ - One or a combination of gallic acid.

4. The method for preparing the carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon. During carbonization, the heating rate is 5 to 10° C. / min, the temperature range is 600 to 800° C., and the carbonization time is 2 to 4 hours.

5. The method for preparing the carbon / magnetic metal / aramid nanofiber composite aerogel absorbing material according to claim 1, characterized in that: The magnetic metal is Fe, Co, Ni or a combination of Fe, Co, Ni and Ni.

Citation Information

Patent Citations

  • Electrospun polyvinyl alcohol-based tannic acid anti-oxidation nanofiber membrane

    CN106319757A

  • Preparation method of nitrogen-modified porous carbon nanofiber aerogel based on aramid nanofiber aerogel

    CN111235699A